Open-rack structure for miniload automated storage and retrieval system:an innovative design approach - Vasili, Mohammadreza; Tang, Sai Hong; Ismail, Napsiah; Sulaiman, Shamsuddin (2008)
Miniload automated storage and retrieval system (AS/RSs) is a type of automatic storage and retrieval system that handles loads that are typically contained in small containers or totes, with load weights typically falling in the 100 to 500 lb. In this paper,the open-rack structure with unidirectional-upward mobile loads within the rack is applied in miniload As/RS, in which the stacker crane is only used for the retrieval operations and the storage operations are carried out by separate devices namely, storage platform for each rack to unload several loads at the same time into the rack. Heuristics algorithms and models are developed for load shuffling and travel time of the storage platform, respectively. The travel time and the Performance of proposed AS/RS is analyzed using Monte Carlo simulation and is compared with a conventional one. The results show that the open-rack AS?RS represents a higher performance and the proposed models are reliable for the design and analysis of this kind of AS/RS.